First Keroplatidae Robsonomyiini (Diptera: Sciaroidea) from the Lowermost Eocene Oise amber (France) - Hebert, Florence; Muller, Valerie Ngô; Nel, Andre (Zootaxa, 2025)
Eokelneria oisensis gen. et sp. nov. a new genus and species of Keroplatidae: Macrocerinae, Robsonomyiini Matile, 1990, is described from the Lowermost Eocene Oise amber. It is the oldest accurate record of this tribe, previously only known by several Middle Eocene Baltic amber species in the genera Kelneria Matile, 1979, Micrepimera Matile, 1990, and Robsonomyia Matile & Vockeroth, 1980.